Optimization of methanol‐induced expression and His‐tag purification of Saccharomycopsis fibuligera R64 mutant α‐amylase in Pichia pastoris - Clara Claudia; Elsa Destiana; Rista Awalia; Mia Tria Novianti; Taufik Ramdani Tohari; Dewi Astriany; Shinta Kusumawardani; Muhammad Yusuf; Umi Baroroh (Universitas Gadjah Mada, 2025)
The Sfamy R64 α‐amylase mutant from Saccharomycopsis fibuligera was expressed in Pichia pastoris to explore its industrial potential. The gene encoding the mutant enzyme was cloned into the pPICZαA vector and transformed into P. pastoris SMD1168. Optimal expression was achieved at 1.5% methanol concentration, with the highest enzyme activity observed at 48 h, reaching 24.06 U/mL. The recombinant protein was purified using Ni‐Sepharose affinity chromatography in native and denaturing conditions. The native conditions retained higher protein integrity and activity, while the denaturing process resulted in partial degradation. Molecular dynamics (MD) simulations conducted to assess the structural stability of the His‐tagged Sfamy R64 α‐amylase mutant and its interaction with the maltose substrate. The simulation confirmed the stable binding of maltose in the active site and the solvent accessibility of the His‐tag, supporting its effectiveness in affinity chromatography. The RMSD, RMSF, and time‐evolution snapshots demonstrated that the protein remained structurally stable over 100 ns at an optimum temperature of 50 °C. The findings suggest that the Sfamy R64 mutant α‐amylase is a promising candidate for industrial applications, combining high expression yields, efficient purification, and stable enzyme‐substrate interactions. The results offer a strong basis for further optimization and large‐scale enzyme production.